IMPLEMENTATION OF KALARIO GAME IN LEARNING PHYSICAL EDUCATION SPORTS AND HEALTH FOR JUNIOR HIGH SCHOOL STUDENTS - Salahuddin, Muhammad; Panai, Abdul Haris; Said, Hariadi; Djafri, Novianty (JURNAL PENDIDIKAN GLASSER, 2024)
Traditional kalario games in penjasorkes learning to increase students' interest and motivation in activities. This research aims to produce educational values and social values in the kalario game as a medium for learning health and health physical education for junior high school students. This game model is expected to increase the educational value of NP4 and social value of NS5 for students. This type of research is Reserch and Development development research. The population in this study were junior high school students in Banggai Regency, the data collection technique used interviews, distributing questionnaires and observations, while the approach used in this study was a qualitative approach with descriptive research type. Research results in kalario games based on educational values and social values. The results of small-scale NP4 observations with an average of 85.67% with good criteria while large-scale NP4 88.83% good criteria, from indicators of sportsmanship assessment, cooperation, responsibility and discipline. Furthermore, the results of observations of the social value of small-scale NS4 were 84.50% with Good criteria, while the social value of large-scale NS4 was 91.38% with Very Good criteria, including indicators of cooperation, communication, sportsmanship, and respect for others